Statistical optimization of compression coated ketoprofen tablet using amylose/ethyl cellulose mixture for colonic delivery - Devi, Nirmala; Sharma, Manju (Journal of Applied Pharmaceutical Research, 2015)
In the present study the effect of two independent factors (amount of ethyl cellulose in coating layer and coating level) on ketoprofen release from compression coated tablet in order to optimize coated tablet for colonic delivery. 3 2 factorial design was used for designing coated formulation. Amount of ethyl cellulose (X1) and coating level (X2) were selected as independent variables. The studied responses were drug release at 5 hr (Y1) and drug release at 10 hr (Y2). The core tablets were compression coated with different ratio of amylose and ethylcellulose. In vitro drug release study was carried out in pH1.2 for 2 hr, pH 7.4 for 3 hr and goat caecal medium for 5 hr. Drug release revealed that amount of ethyl cellulose and coating level have antagonistic effect on drug release. Multiple regression analysis was used for generation of polynomial equation and optimization of formulation. The optimized formulation consisted of ethyl cellulose (14.33 %) and coating level (318 mg) provided a release profile that is closed to estimated values. The model is found to be accurate and robust for optimization of compression-coated tablet for colonic delivery of ketoprofen